A SOCIOPHONETIC STUDY OF DIALECT CHANGE IN IRAQ: THE CASE OF ANAH DIALECT - Yussif, Rusul Riffa’t; Mohammed, Fuad Jasim (Al-Adab Journal, 2023)
This study investigates the occurrence of dialect levelling in the variety of Arabic spoken in Anah, Iraq in terms of the current phonological patterns and change triggered mainly by dialect contact between qeltu and gilit speakers. The study provides a quantitative sociophnetic description of the speech of 60 (30 males and 30 females) Arabic Iraqi Ani (AIA henceforth) speakers. This study investigates the change in two phonological processes: qaf velarisation and Imala (deflexion) under the effect of informants’ age and gender and social network. Following Labov’s (1984) conversational network method, all informants were interviewed individually to collect the linguistic variables required for analysis. Results show that according to the increasing adoption of gilit features by Ani speakers, levelling is occurring in the AIA. Results also revealed that levelling has not yet reached the completion level, yet it is in a very advanced phase.